Specific features of competition functioning of martial arts elite sportsmen - Radchenko, Y. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study competition functioning of martial arts elite sportsmen. Material: we analyzed 33 competition duels, studied specific features of application of 917 technical tactic actions by sportsmen. We used analysis of video-records of competition duels at All-Ukrainian competitions. Results: it was found that modern martial arts are very dynamic kinds of sports. Victory is won usually by versatile sportsmen, who can quickly to re-construct in the course of duel and successfully use strike and wrestling techniques. Most of duels are won by points. Most of sportsmen compete in standing position, preferring striking technique: straight punches in head and side kicks in torso. It was also found that when using wrestling techniques in standing position, sportsmen prefer different throws by legs` gripping. When fighting in lying position sportsmen are successful in holding and try to apply painful holds. Conclusions: results of our researches, providing observations of below described conditions, can be a basis for correction of training process; for choosing of means and methods for coaches and instructors of professional training in Armed Forces and law enforcement bodies.